Urban living labs and the role of users in co-creation. - Menny, Mascha; Palgan, Yuliya Voytenko; McCormick, Kes (Oekom, 2018)
Users as co-creators? We examine how urban living labs (ULLs) effectively engage in a participatory methodology that facilitates co-creation with users, and discuss the link between user involvement and the transformative potential of ULLs. User involvement, governance structure, leadership and power distribution are important factors for ULLs to become transformative. Urban living labs (ULLs) offer opportunities to foster sustainability in cities. They are sites to design, test and learn from innovation in real time. A key element in the operation and success of ULLs is user involvement. Users are often viewed as co-creators who shape ULL outcomes by contributing with their knowledge and experience. The transformative potential of ULLs for sustainability is often interconnected with user participation. Despite its importance, user involvement in ULLs remains a practical challenge that is also understudied. In this article, we examine how ULLs engage in a participatory methodology that facilitates co-creation with users, and discuss the link between user involvement and the transformative potential of ULLs. While co-creation is a cornerstone of the ULL concept, we also show that a combination of different user participation levels in different stages of the ULL life cycle has a potential to enhance the outcomes and transformative potential of ULLs. User involvement plays a positive role in realising the transformative potential of ULLs for sustainability, but governance structure, leadership and power distribution are also important factors for ULLs to become transformative.
Keywords: Nachhaltige Entwicklung; Stadtbewohner; Partizipation; Wissenstransfer; Reallabor; Transdisziplinarität; Forschungsprozess